KERALA Grasim: Polluter Does Not Pay - K M SEETHI (Economic and Political Weekly July 21, 2001, 2001)
The Grasim Industries unit, long tagged the "most pollutant industry in Kerala", has shut shop without paying compensation for the damage it inflicted on the environment. There is also resentment among the workers on the severance package offered, and the lack of social amenities at their workplace.